2004
DOI: 10.1080/09669580408667223
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Tourism Development in Southern Alberta, Canada: Tentative Engagement

Abstract: This paper reviews indigenous/aboriginal tourism, a rapidly evolving sector of the tourism industry and an important growth sector in aboriginal economies, and examines the optimism expressed about its growth potential. Case studies are given of the host, guest and intermediary relationships involved in aboriginal tourism in southern Alberta, Canada, still at an early and tentative stage of development, despite the volume of travel taking place in this area, the location of Canada's largest Indian reserves in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 13 publications
0
39
0
3
Order By: Relevance
“…Conséquemment, cette forme de tourisme lutte pour sa viabilité, non seulement au sein de l'industrie du tourisme, mais aussi dans les environnements socio-économiques et écologiques globaux des collectivités d'accueil. L'écotourisme autochtone est communément caractérisé par l'implication directe des autochtones, soit par l'intermédiaire du contrôle autochtone du produit touristique, soit par des produits touristiques établis en territoire autochtones Notzke, 2004). Les principales caractéristiques de l'éco-tourisme autochtone comprennent : une solide connexion avec la culture autochtone; des produits touristiques détenus et gérés par des autochtones; des produits touristiques provenant de la culture, des environnements et des savoirs traditionnels autochtones; et un tourisme contrôlé (développé, détenu et géré) par les autochtones (Zeppel, 2006).…”
Section: Résumé De L'articleunclassified
See 1 more Smart Citation
“…Conséquemment, cette forme de tourisme lutte pour sa viabilité, non seulement au sein de l'industrie du tourisme, mais aussi dans les environnements socio-économiques et écologiques globaux des collectivités d'accueil. L'écotourisme autochtone est communément caractérisé par l'implication directe des autochtones, soit par l'intermédiaire du contrôle autochtone du produit touristique, soit par des produits touristiques établis en territoire autochtones Notzke, 2004). Les principales caractéristiques de l'éco-tourisme autochtone comprennent : une solide connexion avec la culture autochtone; des produits touristiques détenus et gérés par des autochtones; des produits touristiques provenant de la culture, des environnements et des savoirs traditionnels autochtones; et un tourisme contrôlé (développé, détenu et géré) par les autochtones (Zeppel, 2006).…”
Section: Résumé De L'articleunclassified
“…Malgré ces avantages, le développement de l'écotourisme autochtone au Canada se situe en deçà de son potentiel et est peu considéré dans l'industrie du tourisme autant par les gouvernements que par les collectivités autochtones (Graci, 2010;Notzke, 2004). Relativement peu de produits immédiatement commercialisables sont offerts dans le secteur du tourisme autochtone, particulièrement près des villes carrefours et des principales routes touristiques.…”
Section: Motsunclassified
“…Despite these benefits, Aboriginal ecotourism development in Canada falls short of its potential and is vaguely regarded in the tourism industry, by governments and Aboriginal communities (Graci, 2010;Notzke, 2004). There are relatively few market-ready products in the Aboriginal tourism sector, particularly near gateway cities and major tourism routes.…”
Section: Téoros Special Issue P 65-70 © 2012mentioning
confidence: 99%
“…Studies have identified challenges related to business aspects of development, economic dimensions, institutional factors, and sociocultural challenges (Colton and Whitney-Squire, 2010;Graci, 2010;Hinch and Butler, 2007;Hipwell, 2007;Zeppel, 2006;Notzke, 2004;Altman and Finlayson, 1999). Graci (2010) identified in an exploratory study with key experts in Aboriginal tourism development that a lack of clear understanding and definition of ecotourism; inadequate resources including funding, expertise and support; lack of business and tourism training and education; poor product development and marketing; resistance to sharing culture; and bureaucracies within the community and with investors and partners including requirements for Aboriginal ownership and difficult funding processes are affecting this form of development.…”
Section: Téoros Special Issue P 65-70 © 2012mentioning
confidence: 99%
See 1 more Smart Citation